Risk factors for infection with chikungunya and Zika viruses in southern Puerto Rico: A community-based cross-sectional seroprevalence survey - Adams, Laura E.; Sánchez-González, Liliana; Rodriguez, Dania M.; Ryff, Kyle; Major, Chelsea; Lorenzi, Olga; Delorey, Mark; Medina, Freddy A.; Muñoz-Jordán, Jorge L.; Brown, Grayson; Ortiz, Marianyoly; Waterman, Stephen H.; et al. (PLOS Neglected Tropical Diseases, 2022)
Chikungunya virus (CHIKV) caused a large outbreak in Puerto Rico in 2014, followed by a Zika virus (ZIKV) outbreak in 2016. Communities Organized for the Prevention of Arboviruses (COPA) is a cohort study in southern Puerto Rico, initiated in 2018 to measure arboviral disease risk and provide a platform to evaluate interventions. To identify risk factors for infection, we assessed prevalence of previous CHIKV infection and recent ZIKV and DENV infection in a cross-sectional study among COPA participants. Participants aged 1–50 years (y) were recruited from randomly selected households in study clusters. Each participant completed an interview and provided a blood specimen, which was tested by anti-CHIKV IgG ELISA assay and anti-ZIKV and anti-DENV IgM MAC-ELISA assays. We assessed individual, household, and community factors associated with a positive result for CHIKV or ZIKV after adjusting for confounders. During 2018–2019, 4,090 participants were enrolled; 61% were female and median age was 28y (interquartile range [IQR]: 16–41). Among 4,035 participants tested for CHIKV, 1,268 (31.4%) had evidence of previous infection. CHIKV infection prevalence was lower among children 1–10 years old compared to people 11 and older (adjusted odds ratio [aOR] 2.30; 95% CI 1.71–3.08). Lower CHIKV infection prevalence was associated with home screens (aOR 0.51; 95% CI 0.42–0.61) and air conditioning (aOR 0.64; 95% CI 0.54–0.77). CHIKV infection prevalence also varied by study cluster of residence and insurance type. Few participants (16; 0.4%) had evidence of recent DENV infection by IgM. Among 4,035 participants tested for ZIKV, 651 (16%) had evidence of recent infection. Infection prevalence increased with older age, from 7% among 1–10y olds up to 19% among 41–50y olds (aOR 3.23; 95% CI 2.16–4.84). Males had an increased risk of Zika infection prevalence compared with females (aOR 1.31; 95% CI 1.09–1.57). ZIKV infection prevalence also decreased with the presence of home screens (aOR 0.66; 95% CI 0.54–0.82) and air conditioning (aOR 0.69; 95% CI 0.57–0.84). Similar infection patterns were observed for recent ZIKV infection prevalence and previous CHIKV infection prevalence by age, and the presence of screens and air conditioners in the home decreased infection risk from both viruses by as much as 50%.